A product data manager supporting a new co-design methodology for SMEs. (1st January 2003) - Biondi, Domenico; Bonfatti, Flavio; Monari, Paola Daniela; Giannini, Franca; Monti, Marina
Today, SMEs are often required to provide a fast answer to customer's request for products tailored to its individual requirements; in consequence, it is quite common that SMEs working in the same industrial sector are oriented to cooperate with each other in order to reach a market objective that would be out of reach for a single enterprise, and that can be better achieved from a consortium of enterprises. Often, the cooperation is a real collaboration among the companies in the design of the new product. This paper describes a product data manager supporting the definition and the negotiation of the product data within a co-design network of SMEs. The described tool is part of the results of Esprit Project 25360 COWORK (COncurrent project development IT tools for small medium enterprises netWORKs).